Evaluation of growing media for vegetable seedlings. - Quesada-Roldán, Gustavo (2005)
An agronomic evaluation of vegetable seedlings undergreenhouse conditions was made at the Fabio BaudritMoreno Agricultural Research Station, Alajuela, Costa Rica,from April 12th to May 7th. The selected vegetables tomato,cucumber, broccoli and lettuce were established in plasticcontainers filled with different growing media. When theplants achieved transplant conditions, vigor values,germination, plant development and adobe quality wereevaluated. The substrates that allowed the best tomato,cucumber and broccoli plant development were Juan Viñascompost, earthworm castings + Juan Viñas compost + ricehulk, and Juan Viñas compost + rice hulk. Substrates partiallycomposted of Gmelina arborea sawdust + soil + rice hulk,and peat moss + perlite, were good substrates for the lettuce.The partially composted Gmelina arborea sawdust + coconutcoir + bagasse ashes, Juan Viñas compost + partiallycomposted Gmelina arborea sawdust + rice hulk; and sugarcane bagasse + partially composted Gmelina arborea sawdust+ Juan Viñas compost substrates provided excellent adobequality, although plant development lacked vigour. Thesubstrates fermented soil, coconut coir, commercial substrate2, and sugar cane bagasse + coconut coir + pumice were theworst growing media, constraining plant growth.